Methods in Quaternary Ecology #1. Freshwater Algae - Smol, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1987)
Summary Morphological and biogeochemical remains of past algal populations can be recovered from most sedimentary deposits. The majority of these fossils are diatom valves, but many algal groups are preserved in some form. All algal taxa have specific ecological requirements, and therefore their stratigraphic distributions in sedimentary profiles can be used to infer past environmental conditions. This paper briefly reviews some of the ways that freshwater algal assemblages have been used in paleoecological studies, with an emphasis on North American research.